Becoming the teacher I needed : lessons in radical kindness and resilience - Chang, Jere (Jossey-Bass, 2026)
"Becoming the Teacher I Needed is a powerful blend of memoir and inspiration from Jere Chang--a 20-year classroom veteran and beloved influencer with over 3 million followers. Chang's radical kindness, teacher humor, and authentic storytelling have made her a trusted voice for educators throughout North America. In this book, she shares her personal journey from struggling student to thriving teacher, weaving candid stories with actionable strategies for overcoming burnout, building resilience, and rediscovering joy in the classroom. Readers will find an uplifting, honest guide for teachers who want to feel seen, valued, and inspired"-- Provided by publisher.